Postsecondary Instructors’ Reflective Teaching Practices Pertaining to Gender Differences and Teaching Experience - Almusharraf, Norah; Almusharraf, Asma (Journal of Ethnic and Cultural Studies, 2021)
Reflection and reflective practices are integral to teacher education; therefore, this study contributes to the growing literature on reflective practice by uncovering gender differences. The study explored the influence of gender differences and teaching experience on postsecondary instructors’ conscious reflective teaching practice, using a survey of 226 male and 207 female EFL instructors working in the Kingdom of Saudi Arabia (KSA). The results indicated that females scored higher than males on the total English Language Teaching Reflection Inventory (ELTRI) scores, except on the critical factor of the ELTRI, where males outperformed. The results also revealed that experienced instructor participants had a significantly higher score on the total ELTRI than novice instructor participants. The study proposes a tangible, flexible resource for reflective practices of applied, cognitive, affective, metacognitive, and critical reflection, and offers assistance to counter gender differences. The study recommends designing guides with effective and valid instruments for fostering reflective teaching practices. Policymakers in higher institutions should prepare systematic programs and provide remedial resources and events for instructors to target the most challenging areas for both genders. Future research should also consider other factors, such as the academic degree, cultural background, and linguistic differences that might affect the instructors’ knowledge and reflective practice.